Pola Kepengarangan dan Derajat Kolaborasi Pada Jurnal Perpusdokinfo Terbitan Perpustakaan Nasional Periode 2017-2021 - Rochani Rahayu; Ainun Zakiah Noor (Perpustakaan Universitas Riau, 2022)
Media Pustakawan, Visi Pustaka and Jumantara are all journals published by the National Library of Indonesia with the subject of libraries, documentation and information. The purpose of the study was to determine the pattern of collaboration and the value of the degree of collabobaration in the three journals. The data for the Media Pustakawan jornal is taken from the website, https://ejournal.perpusnas.go.id/mp/, then for Visi Pustaka, is taken from https://ejournal.perpusnas.go.id/vp, and on Jumantara, the site used https://ejournal.perpusnas.go.id./jm. Recording of data in the form of the number of articles, the names of the author and the number of articles, as well as the institutions written in the three journals. Next, the data is grouped by year from 2017 – 2021, the data is processed using simple statistics. Futhermore, the data has bees processed is presented in the form of tables and graphs. The results show that the most articles published during 2017 -2021 are Media Pustakawan (127 titles; 43.34%), followed by Visi Pustaka (91 titles;31.06%) and Jumantara (75 titles; 25.60%). The number of articles written by a single author is 170 titles, consisting of Media Pustakawan with 76 titles 944.70%), Visi Pustaka 50 titles (29.41%) and Jumantara as many as 44 titles (25.89%). The average degree of collaboration for Media Pustakawan is 0.43. Seeing this value, it is concluded that during 2017-2021 single author still dominatate compare to collaborating authors. The most prolific writer is Ahmad Darsa, who wrote 9 articles, and it is known that he came from UNPAD who wrote in the journal Jumantara 13 titles.